Difficulties in communication between daughter-in-law and mother-in-law - Stankowska, Magdalena (Studia Psychologica: Theoria et praxis, 2013)
Communication in the relationship of mother-in-law and daughter-in-law may pose in many families some serious difficulties. The aim of this article is to present the results of a study involving mothers-in-law and daughters-in-law. In this study varies aspects of this relationship were investigated, but in the present article only the results concerning communication are reported on. In total, 53 daughters-in-law and 29 mothers-in-law participated in the study. The research method involved questionnaires and in-depth interviews. The interview results were subjected to a detailed analysis of the four types of difficulties in communication identihed in the research materials: geographical barriers, forms of address, conflict avoidance and discussions on difficult issues, and communication via son/husband. The research results showed that the key obstacles in communications between the mothers-in-law and the daughters-in-law were a lack of willingness to talk openly, avoidance of certain topics and not dealing directly with certain issues.